Effect of Using Agility Ladder Drills on Developing Certain Types of Speed and Skill Performance of the Close-to-the-Net Setup Skill in Volleyball - Ali Hameed Ali Al-Zubaidi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study aimed to identify the impact of designing agility ladder drills and their role in developing types of speed and improving the skill performance of the setup skill in volleyball. The researcher adopted an experimental method using pre- and post-tests over an 8-week training program, with a sample of 10 players from Al-Sahaf Al-Oula Intermediate School in Najaf Al-Ashraf. Statistical analysis (SPSS) revealed that the agility ladder drills contributed to developing specific types of speed among the research sample. Additionally, improvements were observed in speed test results and in the volleyball setup skill performance. The researcher recommends implementing the designed agility ladder exercises for their effectiveness in enhancing agility, flexibility, and coordination, as well as diversifying training methods to develop physical attributes.